High temperature oxidation of rare earth permanent magnets. Part 2–Kinetics. (1st April 2018) - Firdaus, Muhamad; Rhamdhani, M. Akbar; Durandet, Yvonne; Rankin, W. John; McGregor, Kathie
Highlights: Three different oxidation mechanisms of (Nd, Pr)FeB have been identified in the temperature ranges 700–1000 K, 1000–1300 K and 1300–1500 K. At 700–1000 K, the apparent activation energy is 157 kJ mol −1 with possible rate limiting step of O diffusion through α-Fe matrix. At 1000–1300 K, the apparent energy activation is 86 kJ mol −1 with possible rate limiting step of O diffusion through γ-Fe. At 1300–1500 K, the apparent energy activation is 197 kJ mol −1 with possible rate limiting step of combined diffusion of Fe and O through the γ-Fe. Abstract: Oxidation is an integral part of some high temperature recycling routes for rare earth permanent magnets. This paper deals with a study of oxidation kinetics of commercial permanent (Nd, Pr)FeB magnet samples, re-sized to 5 × 5 x 10 mm, in the temperature range 700–1500 K. The results show that the oxidation behaviour follows a parabolic rate law and that the kinetics can be described using the Ginstling–Brounshtein diffusion model. In line with the microstructure study that shows three different oxidation mechanisms, the kinetics study also reveals that there are probably three different rate-controlling mechanisms in the temperature range studied.